2010
DOI: 10.1186/1757-1146-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Non‐ medical prescribing in Australasia and the UK: the case of podiatry

Abstract: BackgroundThe last decade has witnessed a rapid transformation in the role boundaries of the allied health professions, enabled through the creation of new roles and the expansion of existing, traditional roles. A strategy of health care 'modernisation' has encompassed calls for the redrawing of professional boundaries and identities, linked with demands for greater workforce flexibility. Several tasks and roles previously within the exclusive domain of medicine have been delegated to, or assumed by, allied he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 43 publications
0
79
1
Order By: Relevance
“…In the last decade of health care modernization, there has been redrawing of professional boundaries and identities and greater workforce flexibility [1]. Several tasks and roles previously within the exclusive domain of medicine have been delegated to allied health professionals, with the reshaping of workforce to meet the challenges posed by changing demographic, social and political contexts [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade of health care modernization, there has been redrawing of professional boundaries and identities and greater workforce flexibility [1]. Several tasks and roles previously within the exclusive domain of medicine have been delegated to allied health professionals, with the reshaping of workforce to meet the challenges posed by changing demographic, social and political contexts [1].…”
Section: Discussionmentioning
confidence: 99%
“…Several tasks and roles previously within the exclusive domain of medicine have been delegated to allied health professionals, with the reshaping of workforce to meet the challenges posed by changing demographic, social and political contexts [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policy level solutions have emphasised the need for workforce flexibility and an expansion in role boundaries for the allied health professions (AHPs), such as podiatry [1,5,6]. Much of the literature on workforce change in the health professions has focused on extended roles, such as prescribing or podiatric surgery, with little attention paid to the impact of these reforms on generalist practice [7][8][9]. This study aimed to address the issue of role flexibility and reform on non-specialist podiatry practice in the UK, often referred to as general podiatry or 'core' podiatry, through the eyes of expert podiatrists drawn from the ranks of its professional body [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[56] The paper concluded that the changes were met with resistance on the right to access, administer, supply and prescribe medicines from the traditional prescribing workforce. However, the broader policy agenda allowed workforce redesign to continue, and podiatry has assumed wider roles and responsibilities in prescribing.…”
Section: Views On Suitability Of Training As Preparation To Prescribementioning
confidence: 99%